2007
DOI: 10.1038/sj.bjc.6603893
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol and gastric cancer risk in Korean men: the National Health Insurance Corporation Study

Abstract: We investigated the risk of gastric cancer by subsite in relation to cigarette smoking and alcohol in a large population-based cohort of 669 570 Korean men in an insurance plan followed for an average 6.5 years, yielding 3452 new cases of gastric cancer, of which 127 were cardia and upper-third gastric cancer, 2409 were distal gastric cancer and 1007 were unclassified. A moderate association was found between smoking, cardia and upper-third (adjusted relative risk (aRR) 2.2; 95% confidence interval (CI) 1.4 -3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 20 publications
2
64
1
3
Order By: Relevance
“…Studies performed in China showed that eating fast increases the gastric cancer risk (Ji et al, 1998;Sung et al, 2007). Ji et al (1998), found that eating fast increased the risk of cancer of the gastric cardia by 2.7 fold (p < 0.001) and the risk of non-cardia gastric cancer by 1.9 fold (p = 0.043).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed in China showed that eating fast increases the gastric cancer risk (Ji et al, 1998;Sung et al, 2007). Ji et al (1998), found that eating fast increased the risk of cancer of the gastric cardia by 2.7 fold (p < 0.001) and the risk of non-cardia gastric cancer by 1.9 fold (p = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary or eating habits thought to be closely associated with the development of gastric cancer and hence numerous studies in this area have already been conducted (Ji et al, 1998;Cai et al, 2003;Sung et al, 2007). Studies performed in China showed that eating fast increases the gastric cancer risk (Ji et al, 1998;Sung et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection is one of the main risk factors in 65-80% of gastric cancers. (Sung et al, 2007). Some kind of foods, such as smoked foods, salted fish and meat and pickled vegetables are associated with higher risk of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…While GCCs may be related to gastroesophageal reflux (GER), white race, male gender, and tobacco smoking (5), the majority of GNCCs are attributable to chronic Helicobacter pylori infection (6), tobacco smoking (7), consumption of salt and salt-preserved foods (8,9), and alcohol abuse (10).…”
Section: Introductionmentioning
confidence: 99%